2019
DOI: 10.1007/s00198-019-05229-7
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of whole dairy matrix on musculoskeletal health and aging–current knowledge and research gaps

Abstract: Dairy products are included in dietary guidelines worldwide, as milk, yoghurt, and cheese are good sources of calcium and protein, vital nutrients for bones and muscle mass maintenance. Bone growth and mineralization occur during infancy and childhood, peak bone mass being attained after early adulthood. A low peak bone mass has consequences later in life, including increased risk of osteoporosis and fractures. Currently, more than 200 million people worldwide suffer from osteoporosis, with approximately 9 mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 102 publications
0
37
0
2
Order By: Relevance
“…Although the mechanistic pathways by which milk might alleviate inflammation is not completely understood, milk contains nutrients such as calcium, vitamin D, bio active peptides, and linoleic acid, which possess anti-inflammatory properties and act in distinct pathways to mitigate inflammation [ 34 , 35 , 36 ]. However, recent evidence indicates that the impact of dairy on health outcomes cannot be attributed to a single element present in dairy, and the overall nutrient composition or so-called the matrix effect needs to be considered [ 37 ]. Nevertheless, we did not find an association between milk intakes and other inflammatory markers i.e., hs-CRP, IL-6, or adiponectin in children.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanistic pathways by which milk might alleviate inflammation is not completely understood, milk contains nutrients such as calcium, vitamin D, bio active peptides, and linoleic acid, which possess anti-inflammatory properties and act in distinct pathways to mitigate inflammation [ 34 , 35 , 36 ]. However, recent evidence indicates that the impact of dairy on health outcomes cannot be attributed to a single element present in dairy, and the overall nutrient composition or so-called the matrix effect needs to be considered [ 37 ]. Nevertheless, we did not find an association between milk intakes and other inflammatory markers i.e., hs-CRP, IL-6, or adiponectin in children.…”
Section: Discussionmentioning
confidence: 99%
“…The main components of dairy that have been shown to affect the human health are protein (from whey, casein, fragments), fat [saturated/unsaturated, short chain fatty acids (SCFA)], minerals (calcium, magnesium, phosphate), sodium, and sugars (lactose, galactose, glucose) as well as the components of the milk fat globule membrane (MFGM) (i.e., the biological membrane surrounding the lipid droplets in milk) ( 4 ). The final dairy product nutritional value tends to be determined by the milk-based source (age, mammalian-type, feed and lactation stage), processing/preparation type (storage condition, temperature and heat duration) as well as the fermentation and cultures used and any additives ( 5 ). Table 1 shows a list of controlled trials using dairy products to mitigate bone loss and support bone health in adults.…”
Section: Components Of Milk and Dairy Foodsmentioning
confidence: 99%
“…The potential bias by the corporate funding of trials or even speaker fees or travel grants should not be neglected [ 141 , 142 , 143 ]. Of 22 review articles (in English, found in PubMed by the search term “review AND (milk OR dairy) AND (osteoporosis OR fracture)” and limited to those papers with milk, dairy, or other dairy products in the titles published in 2016–2020) published in the past years, 13 papers [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ] were written by at least one author with links to the dairy industry or dairy associations, whereas the authors of nine papers [ 4 , 9 , 10 , 157 , 158 , 159 , 160 , 161 , 162 ] did not report any such conflicts of interest. Although not explored, the proportion of opinion papers, comments, and letters to the editors with conflicts of interest is likely to be higher.…”
Section: Author Autonomy From Dairy Industrymentioning
confidence: 99%